The Effect of Competence on Health Promotors Performance in Central Java Indonesia - Indarjo, Sofwan; Azinar, Muhammad; Raharjo, Bambang Budi; Salma, Wanale Mafabi (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Health Promoter is one of the health professionals in all health institutions. Different educational backgrounds, educational levels, competencies and functional positions can affect performance in the field. This study aims to analyze competence and its effect on the performance of health promoters. This type of research is an exploratory survey with a quantitative approach. The research population is health promoters in Central Java. The research sample was 114 people and selected by simple random sampling technique. Data analysis used simple linear regression. The results showed that there was a strong positive correlation between competence and performance (r = 0.712), the coefficient of determination (R square) was 0.507. This explains that 46.3% of performance is influenced by competence.